Some Cooperatives Produce Great Wines, but the Majority Does Not: Complementary Institutional Mechanisms to Improve the Performance of an Indispensable Organizational Form*. (11th January 2018) - Frick, Bernd
Abstract: Although they have often been found to be technically inefficient, cooperatives not only have survived in the wine industry but continue to play major roles in most European countries. Because the specific advantages of their "organizational architecture" (resource pooling and decentralization) seem to outweigh the disadvantages (vaguely defined property rights and high monitoring costs), this paper discusses organizational measures to improve the performance of cooperatives by addressing three different aspects of "organizational design" (managing entry and exit, motivating members, and investing in corporate culture). (JEL Classifications: D22, D23, L14, L21, L31)